Ionotropic and metabotropic activation of a neuronal chloride channel by serotonin and dopamine in the leech Hirudo medicinalis - Ali, Declan W (Blackwell Science Inc, 1998)
1. Cl(−) channels on the pressure-sensitive (P) neuron in the leech are directly activated by synaptic release of serotonin (5-HT) and are indirectly stimulated by the cAMP second messenger pathway, suggesting an unusual dual regulation of the channels. We have investigated the mode of action of 5-HT and dopamine (DA) on a Cl(−) channel in adult P cells in culture by recording from cell-attached patches. 2. 5-HT increased Cl(−) channel activity only when included in the recording pipette and not when applied in the bath. 3. Pipette or, more effectively, bath application of DA led to an increase in Cl(−) channel activity. This effect was blocked by the potent and specific dopaminergic (DA(1)) receptor blocker, SCH-23390. 4. The stimulation by DA, but not by 5-HT, was also blocked by the cAMP-dependent protein kinase A (PKA) inhibitor Rp-cAMP and was mimicked by the membrane-permeant cAMP analogue dibutyryl cAMP (db-cAMP). 5. Our results show that 5-HT directly gates a Cl(−) channel that is also activated by DA via the cAMP pathway. This study demonstrates that a ligand-gated channel can be independently operated by another transmitter acting via a second messenger pathway.